Artificial muscles, made of dielectric elastomer actuators - a promising solution for inherently compliant future robots - Yoo, In Seong; Reitelshöfer, Sebastian; Landgraf, Maximilian; Franke, Jörg (Springer Berlin Heidelberg, 2015)
The cutting-edge robotic technology can deal with a lot of complex tasks. However, one of the most challenging technological obstacles in robotics is the development of soft actuators. Remaining challenges in the field of drive technology can be overcome with innovative actuator concepts, for example dielectric elastomer actuators (DEAs). DEAs show numerous advantages in comparison to prevailing robotic actuators that are based on geared servomotors: They are formflexible, inherently compliant, can store and recuperate kinetic energy, feature high power-to-weight ratio and high energy density that is comparable to human skeletal muscles, and finally can be designed to perform natural motion patterns other than rotation. In this article, after a review on disadvantages of state-of-art robotic drives, which are stimulus for a research on the promising drive solution, benefits of DEAs will be presented with regard to the possibility of applications in soft robotics. Finally, the article will conclude with a brief report on the ongoing research effort at the Institute for Factory Automation and Production Systems (FAPS) with two major foci – the development of an automated manufacturing process for stacked DEAs and a lightweight control hardware.
CRIS-Team Scopus Importer:2023-03-07